2021
DOI: 10.2139/ssrn.3775537
|View full text |Cite
|
Sign up to set email alerts
|

Informed Choices: Gender Gaps in Career Advice

Abstract: This paper estimates gender differences in access to informal information regarding the labor market. We conduct a large-scale field experiment in which real college students seek information from 10,000 working professionals about various career paths, and we randomize whether a professional receives a message from a male or a female student. We focus the experimental design and analysis on two career attributes that prior research has shown to differentially affect the labor market choices of women: the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This finding aligns with previous research suggesting that females may experience greater anxiety when making career-related decisions due to societal expectations, stereotypes, and perceived barriers in certain professions (Landaud et al, 2020). For instance, a study by Gallen and Wasserman (2021) revealed that female high school students reported more career exploration anxiety concerning factors such as job security, work-life balance, and societal expectations than did their male counterparts. These anxieties could be attributed to the same societal factors influencing career choices in adults, such as gender stereotypes (Kimaro & Lawuo, 2016) that portray certain professions as less suitable for females, even at the high school level, and perceived barriers (Landaud et al, 2020), such as unconscious bias in educational guidance or lack of female role models in specific fields, which could heighten anxieties about navigating those career paths.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding aligns with previous research suggesting that females may experience greater anxiety when making career-related decisions due to societal expectations, stereotypes, and perceived barriers in certain professions (Landaud et al, 2020). For instance, a study by Gallen and Wasserman (2021) revealed that female high school students reported more career exploration anxiety concerning factors such as job security, work-life balance, and societal expectations than did their male counterparts. These anxieties could be attributed to the same societal factors influencing career choices in adults, such as gender stereotypes (Kimaro & Lawuo, 2016) that portray certain professions as less suitable for females, even at the high school level, and perceived barriers (Landaud et al, 2020), such as unconscious bias in educational guidance or lack of female role models in specific fields, which could heighten anxieties about navigating those career paths.…”
Section: Discussionsupporting
confidence: 88%
“…This could stem from difficulties within individuals or the characteristics of professions, which may lead students to limit their exposure to career information or constrain their capabilities (Landaud et al, 2020). Additionally, other demographic factors, such as gender (Gallen & Wasserman, 2021), grade level, and academic performance (Nguyen-Thi et al, 2024), influenced career decisionmaking anxiety among high school students.…”
Section: Introductionmentioning
confidence: 99%